Mengembangkan Budaya Jawa Terhadap Kebiasaan Masyarakat Desa Wisata Jungsemi, Kecamatan Kangkung, Kabupaten Kendal, Jawa Tengah - Imanina, Almas Nabili; Jannah, Desika Nur; Arvianto, Bram; Susitaningrum, Inggrit; Hartanu, Devira Aprillia (JURNAL KEPARIWISATAAN, 2024)
One of the areas that still try to preserves Central Javanese culture is Jungsemi Tourism Village, Kangkung District, Kendal Regency, Central Java. Various kinds of culture are still preserved in the village, one of which is the Merdi Deso tradition. This is done by the community to preserve regional arts, culture and local wisdom inherited from the ancestors of the Indonesian people. This research was conducted using descriptive qualitative methods and through observations and interviews and concepts from Ife (2014) regarding components of cultural development for data collection with the aim of finding out what cultures can be developed. Based on research results, the Jungsemi tourist village does not yet have its own local specialties, traditional dances and traditional clothing and still relies on Indah Kemangi Beach to become a leading tourist attraction, but the Jungsemi Tourism Village does not close itself off from continuing to learn and develop in order to maintain tourism to improve local economy income.